COLLABORATIVE COMMUNICATION IN TALENT MAPPING OF CHILDREN WITH SPECIAL NEEDS IN INCLUSION SCHOOL - Pramesti Anindyawardhani, Satwika; Noegroho, Agoeng; Runtiko, Agus Ganjar (Jurnal Sosial Humaniora, 2023)
The talents of children with special needs (ABK) that are detected and developed can become life skills. In the future, it is these life skills that make ABK productive, independent and able to contribute to their social environment. However, it requires the support and collaboration of parents and schools in recognizing and stimulating children’s talents. This study aims to describe the process of collaborative communication between inclusive schools and parents in mapping ABK talent at the Baturraden Nature School, Purwokerto. Research using case study method. Data collection techniques were carried out by observation, interviews and documentation. Data were analyzed using Miles and Huberman’s model. The results of the study show that Baturraden Nature School builds collaborative communication with parents of ABK students through dialogue, building trust, commitment and sharing understanding. Collaborative communication is carried out interpersonally and in groups through various activities, school programs and the use of communication media. Collaborative communication plays an important role in mapping ABK student talents. In the process found inhibiting factors and obstacles in collaborating. These obstacles should be overcome with intense dialogue, changes in behavior and mutually agreed solutions.